The 3D Story - Thabet, Tamer (Eludamos: Journal for Computer Game Culture, 2008)
This reading attempts to show how Iron Storm connects history and fiction by means of a three-dimensional storytelling system. This paper further explores new limits of game concepts such as Jenkins space architecture and Murray's immersion, and directed towards the testing of an experientail approach to game narrative and play analysis.